Directing playfully: Towards an understanding of the practical knowledge involved in leading multi-family groups for adults with severe eating disorders - Balmbra, Steven Macgregor (Universitetet i Nordland, 2014)
Masteroppgave i praktisk kunnskap - Universitetet i Nordland, 2014